An Integration that Does Not Integrate: A Look at the Energy Experience at Unasur - Briones, Yessenia Paola (2023)
Given the strategic importance of energy in increasing productivity and improving the standard of living of a society; In recent years, integration projects in South America have incorporated this resource as an essential element for development. In fact, with the signing of the Unasur constitution treaty, in 2008, a regional strategy began with a view to institutionalizing the energy regime to involve all countries that are already participants in this scheme. However, the region has not been able to move from official statements to policy implementation. Thus, in this article it is argued that there are three obstacles that converge and persist in South American regionalism: institutional flexibility, heterogeneity in the margins of agency and overlapping of regional organizations. Likewise, within the framework of the dissolution of Unasur, some perspectives are offered for the energy project in the region.